Potential Prebiotic Properties of Crude Polysaccharide Extract from Durian (Durio zibethinus Murr.) Seed Flour - Varichanan, Patthinan; Shompoosang, Sirinan; Dueramae, Sawitree (Trends in Sciences, 2023)
The purpose of this research is to investigate the possible presence of prebiotic substances in durian seeds. The durian seed flour (DSF) was prepared by drum dry processing at 140 °C. The proximate composition of DSF 100 g contained moisture (2.43 g), protein (6.85 g), total fat (0.60 g), total carbohydrate (87.73 g), ash (2.39 g), and the sum of dietary fiber (4.48 g), respectively. The morphology of DSF was studied by SEM at a fixed magnification (100×). DSF appears to have smooth and rough surfaces, and the granules are covered by the gum. The optimal condition for extracting crude polysaccharide from DSF is ethanol 50 % at solvent ratios 1:8 at a temperature of 30 °C for 90 min, gave a maximum extraction yield of 5.28 % and the maximum amount of non-reducing sugar content at 392.19 ± 10.60 mg mL−1. The amount of non-reducing sugar is represented by an oligosaccharide referred to as a prebiotic. After being digested in vitro, the crude polysaccharide extract and inulin each had a total percentage of hydrolysis that was 14.68 and 11.54 %, respectively. Thus, approximately 85.32 % of crude polysaccharide extract was estimated to reach the colon. Moreover, the crude polysaccharide extract has enhanced activity values higher than inulin with 3 probiotic strains. The enhanced activity value increases when the extract concentration increases. The concentration of crude polysaccharide extract was 5.0 %w/v. Lactobacillus rhamnosus TBRC 374 had the highest enhanced activity at 582.67 %. In comparison, Lactobacillus casei BCC 13300 and Lactobacillus acidophilus ATCC 4356 with enhanced activity were 543.78 and 288.34 %, respectively. Significant advancements have been made in the utilization of plant waste and the development of novel prebiotic ingredients with the potential for application in food as a result of this research. HIGHLIGHTS Durian seed is one of the wastes that still has a good source of nutrition. Durian seed flour was prepared by drum dry processing that can maintain fiber and texture, making it suitable for application in the food industry. Moreover, the crude polysaccharide extract showed prebiotic properties. These are good prebiotic candidates that might be useful in producing functional foods. GRAPHICAL ABSTRACT